Strategi Pemasaran Dalam Meningkatkan Hasil Penjualan Roti Al-Batsit Melalui Media Sosial ( Studi Kasus Al-Batsit Bakery Di jalan Merawan, Sawah Lebar, Kota Bengkulu) - Putra, Deko Agenty; Oktasari, Emelia; Lestari, Muji; Rahman, Abdul (Jurnal Dehasen Mengabdi, 2022)
This study aims to determine the marketing strategy to increase sales results in the al-batsit bakery business. According to Lion Rimbun in Andreas (2010:38) the definition of quantitative methodology is a procedure that produces descriptive data in the form of research or oral data from people and observable behavior. This research is descriptive qualitative using primary and secondary data sources, while the data collection techniques used are in-depth interviews (in-depth interviews), observation and documentation. Direct face-to-face marketing strategy or word of mouth system, the business should be in marketing products using social media.